Answer:
case a)
----> open up
case b)
----> open down
case c)
----> open left
case d)
----> open right
Step-by-step explanation:
we know that
1) The general equation of a vertical parabola is equal to
![y=a(x-h)^{2}+k](https://tex.z-dn.net/?f=y%3Da%28x-h%29%5E%7B2%7D%2Bk)
where
a is a coefficient
(h,k) is the vertex
If a>0 ----> the parabola open upward and the vertex is a minimum
If a<0 ----> the parabola open downward and the vertex is a maximum
2) The general equation of a horizontal parabola is equal to
![x=a(y-k)^{2}+h](https://tex.z-dn.net/?f=x%3Da%28y-k%29%5E%7B2%7D%2Bh)
where
a is a coefficient
(h,k) is the vertex
If a>0 ----> the parabola open to the right
If a<0 ----> the parabola open to the left
Verify each case
case a) we have
![x^{2}=3y](https://tex.z-dn.net/?f=x%5E%7B2%7D%3D3y)
so
![y=(1/3)x^{2}](https://tex.z-dn.net/?f=y%3D%281%2F3%29x%5E%7B2%7D)
![a=(1/3)](https://tex.z-dn.net/?f=a%3D%281%2F3%29)
so
![a>0](https://tex.z-dn.net/?f=a%3E0)
therefore
The parabola open up
case b) we have
![x^{2}=-10y](https://tex.z-dn.net/?f=x%5E%7B2%7D%3D-10y)
so
![y=-(1/10)x^{2}](https://tex.z-dn.net/?f=y%3D-%281%2F10%29x%5E%7B2%7D)
![a=-(1/10)](https://tex.z-dn.net/?f=a%3D-%281%2F10%29)
![a](https://tex.z-dn.net/?f=a%3C0)
therefore
The parabola open down
case c) we have
![y^{2}=-2x](https://tex.z-dn.net/?f=y%5E%7B2%7D%3D-2x)
so
![x=-(1/2)y^{2}](https://tex.z-dn.net/?f=x%3D-%281%2F2%29y%5E%7B2%7D)
![a=-(1/2)](https://tex.z-dn.net/?f=a%3D-%281%2F2%29)
![a](https://tex.z-dn.net/?f=a%3C0)
therefore
The parabola open to the left
case d) we have
![y^{2}=6x](https://tex.z-dn.net/?f=y%5E%7B2%7D%3D6x)
so
![x=(1/6)y^{2}](https://tex.z-dn.net/?f=x%3D%281%2F6%29y%5E%7B2%7D)
![a=(1/6)](https://tex.z-dn.net/?f=a%3D%281%2F6%29)
![a>0](https://tex.z-dn.net/?f=a%3E0)
therefore
The parabola open to the right